A GalNAc/Gal-specific lectin from the sea mussel Crenomytilus grayanus modulates immune response in macrophages and in mice - Oleg V. Chernikov (Nature Portfolio, 2017)
Abstract A GalNAc/Gal-specific lectin (CGL) from the edible mussel Crenomytilus grayanus has been demonstrated to exhibit antibacterial properties. However, the mechanism of immune modulation by CGL in mammalian cells remains unclear. Here, we demonstrated that CGL can activate immune responses in macrophages and in mice. In the in vitro cell models, CGL induced tumour necrosis factor-α and interleukin-6 secretion in mouse RAW264.7 macrophages, mouse bone marrow-derived macrophages, human THP-1 macrophages, human peripheral blood mononuclear cells and human blood monocyte-derived macrophages. The CGL-mediated cytokine production was regulated by reactive oxygen species, mitogen-activated protein kinases, protein kinase C-α/δ and NF-κB. Interestingly, in lipopolysaccharide-activated macrophages, CGL induced endotoxin tolerance (characterized by the downregulation of nitric oxide, inducible nitric oxide synthase, interleukin-6 and cyclooxygenase II) via the downregulation of IRAK2 expression, JNK1/2 phosphorylation and NF-κB activation. CGL also slightly increased the bactericidal activity of macrophages and induced cytokine production in mouse models. Overall, our data indicate that CGL has the potential to be used as an immune modulator in mammals.